Critical Interpellation and Collectivism in Accelerating the Development of the Rebana Region - Liza Dwi Ratna Dewi (Green Publisher Indonesia, 2025)
This research critically examines Presidential Regulation No. 87 of 2021, which addresses the accelerated development of the Rebana region in Indonesia. Using Louis Althusser's concept of interpellation and Friedrich Hayek's critique of collectivism, the study explores the ideological and structural frameworks embedded in the regulation. The analysis reveals a centralization of power favoring investors, as evident in the prioritization of infrastructure development and minimal attention to community welfare. While the regulation is justified under Article 4, Section 1 of the Indonesian Constitution, it neglects Article 33, which emphasizes economic equity and collective prosperity.Methodologically, the study combines critical textual analysis with qualitative case studies, focusing on community responses in Jatiwangi, a historically significant area within the Rebana region. Findings highlight a significant power imbalance, with communities coerced into industrial conformity, undermining their traditional livelihoods and cultural heritage. Resistance movements, such as the Jatiwangi Festival, illustrate local efforts to reclaim autonomy and advocate for sustainable development. The study concludes by emphasizing the need for economic planning grounded in Pancasila's humanistic philosophy, ensuring equitable development and community participation. It critiques centralized, investor-centric approaches and advocates for a balanced policy framework that respects individual rights and local agency.